Current clinical advances and future perspectives in the psychiatry/mental health field of Latin America (2010)
The history of Mental Health in Latin America is relatively young. It dates back to the mid nineteenth century and widely developed during the twentieth century, with formidable scientific, social, political, and ethical challenges. Latin American psychiatry has contributed in the fields of epidemiology, phenomenology, social psychiatry, psychiatric and epistemological research, and clinical genetics as well. More recent advances can also be seen in clinical psychotherapy and psychopharmacology. Now, there is a formal and informal recognition of various areas of expertise, such as children and adolescents, addictions, anxiety disorders, among others. However, we need to solve the health problems resulting from mental illnesses as well as the disorders related to the social, environmental, political, and economic factors of a continent marked by the precariousness of underdevelopment, which have a high impact on population health. Therefore, considering and trying to minimize the impact of those factors, contributing to the destigmatization of mental illnesses and their consequences, together with the growing number of non-governmental organizations (NGOs), human rights defenders, public figures, etc., and collaborating in building a society that guarantees the right to mental health and adequate treatment and rehabilitation are part of our present challenges in Latin America. © 2010 Institute of Psychiatry.